Grain boundary serration in nickel alloy inconel 600: quantification and mechanisms - Tang, YT; Karamched, P; Liu, J; Haley, JC; Reed, RC; Wilkinson, AJ (Elsevier, 2019)
The serration of grain boundaries in Inconel 600 caused by heat treatment is studied systematically. A new method based on Fourier transforms is used to analyse the multiple wave-like character of the serrated grain boundaries. A new metric – the serration index – is devised and utilised to quantify the degree of serration and more generally to distinguish objectively between serrated and non-serrated boundaries. By considering the variation of the serration index with processing parameters, a causal relationship between degree of serration and solution treatment/cooling rate is elucidated. Processing maps for the degree of serration are presented. Two distinct formation mechanisms arise which rely upon grain boundary interaction with carbides: (i) Zener-type dragging which hinders grain boundary migration and (ii) a faceted carbide growth-induced serration.